Role of Substitutions in the Hemagglutinin in the Emergence of the 1968 Pandemic Influenza Virus - Van Poucke, Sjouke (J Virol, 2015)
Hemagglutinin (HA) of H3N2/1968 pandemic influenza viruses differs from the putative avian precursor by seven amino acid substitutions. Substitutions Q226L and G228S are known to be essential for adaptation of avian HA to mammals. We found that introduction of avian-virus-like amino acids at five other HA positions (positions 62, 81, 92, 144, and 193) of A/Hong Kong/1/1968 virus decreased viral replication in human cells and transmission in pigs. Thus, substitutions at some of these positions facilitated emergence of the pandemic virus.